PENGEMBANGAN BAHAN AJAR KOMIK DIGITAL BERBASIS AUGMENTED REALITY BERBANTUAN APLIKASI CANVA PADA MATERI SISTEM PENCERNAAN SISWA KELAS V SD - Mustika Tanjung Al Hudaya; I Ketut Suastika; Sri Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological developments have encouraged the integration of Augmented Reality (AR) in education, including at the elementary school level, where various efforts have been made to support students' understanding of the digestive system. This material is important in IPAS, but it is still difficult for fifth-grade students to understand. This study aims to develop AR-based digital comic teaching materials using the canva application for digestive system material. Therefore, this study is classified as a development study. The stages in this development use the ADDIE model. The purpose of this study is to measure the validity, practicality, and effectiveness of AR-based digital comic teaching materials. The instruments used are a validation sheet (validity), teacher and student response questionnaires (practicality), and pre-tests and post-tests (effectiveness). The research subjects were teachers and 24 fifth-grade students at SDN Kaliboto Lor 07 through field trials. The validation results showed a percentage of 97.5% from media experts, 90% from subject matter experts, and 100% from language experts, with an average of 95.83% (highly valid). The practicality was rated at 99% by students and 100% by teachers (very practical). Effectiveness was indicated by an N-Gain value of 0.65 (moderate category). Based on these results, the AR-based digital comic was declared to be highly valid, very practical, and effective for use in learning.